2022
DOI: 10.1101/2022.04.07.487583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical Modeling of Rhesus Cytomegalovirus (RhCMV) Placental Transmission in Seronegative Rhesus Macaques

Abstract: Approximately 1 in 200 infants is born with congenital cytomegalovirus (CMV), making it the most common congenital infection. About 1 in 5 congenitally-infected babies will suffer long-term sequelae, including sensorineural deafness, intellectual disability, and epilepsy. CMV infection is highly species-dependent, and the Rhesus CMV (RhCMV) infection of rhesus monkey fetuses is the only animal model that replicates essential features of congenital CMV infection in humans, including placental transmission, feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
3
3
Order By: Relevance
“…Importantly, the rhesus macaque model of cCMV transmission following primary RhCMV infection at the end of 1 st trimester in immunocompetent dams and utilizing the end point of virus detected in AF between 2 and 12 weeks after infection accurately modeled the epidemiology of human CMV transmission following acute infection during pregnancy, with 5 of 12 dams (41.7%) with virus detection in AF [ 3 ]. Yet, contrary to our expectations and challenging a common hypothesis in the field [ 17 , 29 ], we found that maternal plasma VL magnitude and kinetics were not significantly different between AF-positive and AF-negative immunocompetent dams. While the exact mechanism of transplacental CMV transmission has not been fully defined, the notion that more virus circulating in maternal blood leads to greater risk of transmission due to the increased interaction of CMV with the maternal-fetal interface is not supported by these results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Importantly, the rhesus macaque model of cCMV transmission following primary RhCMV infection at the end of 1 st trimester in immunocompetent dams and utilizing the end point of virus detected in AF between 2 and 12 weeks after infection accurately modeled the epidemiology of human CMV transmission following acute infection during pregnancy, with 5 of 12 dams (41.7%) with virus detection in AF [ 3 ]. Yet, contrary to our expectations and challenging a common hypothesis in the field [ 17 , 29 ], we found that maternal plasma VL magnitude and kinetics were not significantly different between AF-positive and AF-negative immunocompetent dams. While the exact mechanism of transplacental CMV transmission has not been fully defined, the notion that more virus circulating in maternal blood leads to greater risk of transmission due to the increased interaction of CMV with the maternal-fetal interface is not supported by these results.…”
Section: Discussioncontrasting
confidence: 99%
“…We reasoned that increased virus circulation in the maternal blood should result in a greater viral load (VL) at the maternal-fetal interface, increasing the likelihood of placental infection and congenital transmission. This idea has recently been supported by mathematical modeling of vertical CMV transmission [ 17 ]. Furthermore, we hypothesized that maternal virus-specific functional antibody responses such as neutralization, antibody dependent cellular cytotoxicity (ADCC), and antibody dependent cellular phagocytosis (ADCP) are important for controlling viral replication and preventing vertical transmission, as cell-to-cell spread is a key mechanism for CMV dissemination [ 18 ], meaning that antibody functions that target both cell-free and cell-associated virus may be needed for adequate control.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the rhesus model of cCMV transmission following primary RhCMV infection at the end of 1 st trimester in immunocompetent dams and utilizing the end point of virus detected in AF fluid between 2 and 12 weeks after infection accurately modeled the epidemiology of human CMV transmission following acute infection during pregnancy, with 5 of 12 dams (41.7%) with virus detection in AF (3). Yet, contrary to our expectations and challenging a common hypothesis in the field (17,25), we found that maternal plasma VL magnitude and kinetics were not significantly different between AF-positive and AF-negative immunocompetent dams. While the exact mechanism of transplacental CMV transmission has not been fully defined, the notion that more virus circulating in maternal blood leads to greater risk of transmission due to the increased interaction of CMV with the maternal-fetal interface is not supported by these results.…”
Section: Discussioncontrasting
confidence: 70%
“…We reasoned that increased virus circulation in the maternal blood should result in a greater viral load at the maternal-fetal interface, increasing the likelihood of placental infection and congenital transmission. This idea has recently been supported by mathematical modeling of vertical CMV transmission (17). Furthermore, we hypothesized that maternal virus-specific functional antibody responses such as neutralization, antibody dependent cellular cytotoxicity (ADCC), and antibody dependent cellular phagocytosis (ADCP) are important for controlling viral replication and preventing vertical transmission, as cell-to-cell spread is a key mechanism for CMV dissemination (18), meaning that antibody functions that target both cell-free and cell-associated virus may be needed for adequate control.…”
Section: Introductionmentioning
confidence: 90%
“…While the dosing and frequency of hyperimmune globulin also differed in these studies, a positive effect was only observed in women with very early infection, pointing to the potential importance of accuracy in the dating of infection recency. Recent studies have started to explore the role that antibody responses play in CMV transmission in a rhesus macaque model 61,62 . However, data in humans is limited and often confounded by the differing risk of infection associated with primary as compared to non-primary infection 63 .…”
Section: Discussionmentioning
confidence: 99%